Foreign interventions and abuse of civilians during the Peruvian civil war - David Fielding; Anja Shortland (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The international community has a declared intention to protect innocent civilians from direct and deliberate violence in civil conflicts, but its track record of actually doing so is mixed. Using a new monthly time-series data set, we explore the factors associated with variations in the number of civilians killed or wounded by participants in the civil war in Peru during the 1980s and 1990s. We find that an increase in the level of abuse by one side is strongly associated with subsequent increases in the level of abuse by the other. Certain types of foreign intervention had a large and statistically significant impact on the level of abuse; some types of intervention raised the level of violence, but others reduced it.
Keywords: 330; Peru; civil war; conflict; abuse against civilians; Bürgerkrieg; Bevölkerung; Sicherheitspolitik; Peru